2013
DOI: 10.1039/c3ra44734k
|View full text |Cite
|
Sign up to set email alerts
|

BMP2-loaded nanoporous silica nanoparticles promote osteogenic differentiation of human mesenchymal stem cells

Abstract: Nanoporous (or mesoporous) silica materials have been extensively investigated as a novel biomaterial in the last few years, especially with regard to bone tissue engineering. Due to their high specific surface areas, capability for chemical modification, and their large pore volumes, nanoporous silica nanoparticles (NPSNPs) are of tremendous interest as drug delivery systems. In this study, we describe the immobilization of the bone growth factor BMP2 on NPSNPs in biologically relevant amounts, using coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 64 publications
3
40
0
Order By: Relevance
“…In addition, silica can be easily functionalized, for instance, to modify surface properties and link therapeutic molecules. Indeed, MSNs containing immobilized bone growth factor (BMP-2) on their surface promoted osteogenic differentiation of hMSCs [21]. Zhou et al expanded this approach by in addition to immobilizing BMP-2 on the surface also loading dexamethasone (DEX) into the pores of the particle.…”
Section: Delivery Of Growth Factors Using Nanoparticlesmentioning
confidence: 99%
“…In addition, silica can be easily functionalized, for instance, to modify surface properties and link therapeutic molecules. Indeed, MSNs containing immobilized bone growth factor (BMP-2) on their surface promoted osteogenic differentiation of hMSCs [21]. Zhou et al expanded this approach by in addition to immobilizing BMP-2 on the surface also loading dexamethasone (DEX) into the pores of the particle.…”
Section: Delivery Of Growth Factors Using Nanoparticlesmentioning
confidence: 99%
“…The nanoporous silica nanoparticles (NPSNPs) were synthesized according to an adapted literature procedure of Neumann and co-workers [29,39]. They exhibited a spherical morphology and a narrow polydispersity with a mean diameter of 40 nm (Figure 2).…”
Section: Modified Nanoporous Silica Nanoparticlesmentioning
confidence: 99%
“…Nanoporous silica nanoparticles (NPSNPs), in particular, are of great interest to drug delivery, because their size [27][28][29], shape [30][31][32][33][34][35] and surface modification [36][37][38] can be adjusted. NPSNPs can easily be synthesized via the sol-gel route with surfactants as structure-directing agents [39]. These cytotoxic molecules are completely removable by calcination at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that increasing the pore diameter of MSNs increases the drug delivery rate. 101 Neumann et al 102 have prepared BMP2-functionalized nanoporous silicon NPs (NPSNPs) using a coupling method via an aminosilane linker. The NPs have an average size ranging from 30 to 50 nm (pore sizẽ 2.8 nm), and the loading efficiency of BMP-2 loaded-NPSNPs was~0.99 μg mg − 1 .…”
Section: Mesoporous Silica Nps As Gf Carriersmentioning
confidence: 99%